Performance testing of a cross-flow membrane-based liquid desiccant dehumidification system - Bai, Hongyu; Zhu, Jie; Chen, Ziwei; Ma, Lina; Wang, Ruzhu; Li, Tingxian (Elsevier, 2017)
A membrane-based liquid desiccant dehumidification system is one of high energy efficient dehumidification approaches, which allows heat and moisture transfers between air stream and desiccant solution without carryover problem. The system performance is investigated experimentally with calcium chloride, and the impacts of main operating parameters on dehumidification effectiveness (i.e. sensible, latent and total effectiveness) are evaluated, which include dimensionless parameters (i.e. solution to air mass flow rate ratio m∗ and number of heat transfer units NTU) and solution properties (i.e. concentration Csol and inlet temperature Tsol,in). The sensible, latent and total effectiveness reach the maximum values of 0.49, 0.55, and 0.53 respectively at m∗= 3.5 and NTU = 12, and these effectiveness are not limited by m∗ and NTU when m∗ > 2 and NTU > 10. Both the latent and total effectiveness increase with Csol , while almost no variation is observed in the sensible effectiveness. All effectiveness can be improved by decreasing Tsol,in. The experimental data provide a full map of main design parameters for the membrane-based liquid desiccant air conditioning technology.